Optimization and reduction of industrial load in a wastewater basin - Kanat, Gurdal; Yeter, Derya (ELSEVIER SCIENCE INC, 2020)
In this study, a method for specification and reduction of industrial wastewater load has been determined in a wastewater basin. The operation of industrial pre-treatment plants is not very efficient in the basin and causes operational problems both in sewer and central treatment plants. Also, heavy metals from anthropogenic activities are among the most widespread pollutants. However, there is a few research for the heavy metals reaching the treatment plants from the urban sewer. In the study, a comprehensive survey and analysis study was carried out for 20 parameters of the industries with the highest load. These parameters were found to have a burden on the municipal wastewater treatment plant at rates ranging from 85% to 99%. By the proposed load reduction method, approximately 99% of the industrial wastewater could be treated and discharged at the legislation limits in the study basin. The reduction in the pollutant load was also examined in detail by two parameters and it was calculated that the organic load will be decreased to 6,331 kgCOD/d (chemical oxygen demand) as 85% and, Zn to 6.8 kg/d with a 94% decrease. The findings of the study clearly indicated that the removal of a higher amount of pollutants is achieved with the use of fewer industrial wastewater pre-treatment plants and the protection of the environment is ensured.
Keywords: Basin; Characterization; Industrial; Optimization; Pollutant; Wastewater; HEAVY-METALS; SURFACE SEDIMENTS; AQUEOUS-SOLUTIONS; ECOLOGICAL RISK; RIVER ESTUARY; MARMARA SEA; URBAN; ISTANBUL; SPECIATION; CONTAMINATION; Engineering; Water Resources